Pekerja Sosial Dalam Menangani Kasus Perundungan (Bullying) Terhadap Anak Melalui Cognitive Behavioral Therapy - Andrio Ramadhan; Ati Kusmawati; Herlambang Trianto; Pritty Dwi Arlista (Concept: Journal of Social Humanities and Education, 2024)
This article aims to explain and describe social work in handling cases of bullying in children through cognitive behavioral therapy. The discussion in this article was obtained through literature studies from various reading sources such as journals and books which were used to explain theories related to bullying and cognitive behavioral therapy. The current lack of education and handling of bullying is the trigger for the increasing number of bullying cases that occur every year, this shows the importance of handling bullying cases. In this case, the role of social work includes, among others, as a broker, enabler, advocate and motivator. Apart from that, in cases of child bullying through cognitive behavioral therapy, social work as a counselor plays a role in helping the learning process to create conventions in such a way that clients can change their behavior and solve their problems. By looking at the benefits of behavioral counseling mentioned above, researchers hope to minimize bullying.